Expert System For Diagnostic Disease Of Cultivation Of Cucumber Holticulture Using Certainty Factor Method Based On Web-Based - Dhea Armaya; Budi Serasi Ginting; Yani Maulita (CV. AFDIFAL MAJU BERKAH, 2022)
Indonesia is an agrarian country where most of the population earn a living as farmers, including cucumber farmers. The biggest threat to cucumber farmers is the presence of diseases that attack their cucumber plants. What often happens is that there are many losses due to cucumber plant diseases that are too late to detect and have reached a severe stage, causing crop failure. To identify a disease disorder on cucumber plants, an expert on cucumber plant diseases is needed in diagnosing symptoms of disease disorders that attack cucumber plants. The distance traveled by experts to find out cucumber plant diseases at the Department of Agriculture of Langkat Regency is difficult so that it makes farmers experience losses and it is difficult to diagnose diseases in cucumber horticultural crops. For that reason, so in this study an expert system was built to diagnose diseases in cucumber horticulture crops. This expert system has 7 diseases and 16 symptoms . The Certainty Factor method was chosen because it is able to provide a level of confidenceexpert on the problem at hand. Based on the results of the Certainty Factor calculation, the highest confidence value is found in powdery mildew and rotten fruit with a value of 0.6 with a value of 60%. From the results obtained, the system diagnosed that the plant was affected by powdery mildew and rotten fruit.